Weediness of spring barley crops depending on the forecrop in the Eastern Forest-Steppe of Ukraine - R. Hutianskyi; S. Popov; N. Kuzmenko; V. Bezpalko (Карантин і захист рослин)
Goal. To determine the species composition of weeds, their dominant role, and to establish the type and level of weediness of spring barley crops grown after sugar beet, corn for grain ½ + soybean ½ and spring barley as forecrops in the conditions of the Eastern Forest-Steppe of Ukraine.